Meru Tejakula: Beach Club and Resort - Zulfikar Wijaya (Jurnal Poster Pirata Syandana, 2026)
A TROPICAL SANCTUARY INSPIRED BY THE RICH HERITAGE OF INDONESIA. WHERE CONTEMPORARY DESIGN MEETS NATURAL BEAUTY, CREATING UNFORGETTABLE EXPERIENCES IN EVERY MOMENT.